PENYELESAIAN SENGKETA HIBAH TANAH DI PENGADILAN AGAMA KRAKSAAN: (Studi Di Pengadilan Agama Kraksaan Perkara Nomor : 2308/Pdt.G/2016/Pa.Krs) - H.A. DJAZIM MA'SHUM; Ali Hurozim (JUSTNESS - Jurnal Hukun dan Agama, 2022)
Abstraction Within the scope of the Religious Courts, the cases handled by the basic courts used not only positive law but also Islamic law, such as in the case of grant disputes. Literally the grant comes from the word wahaba-yahabu-hibatan, which means to give or give, and is a management contract for the provision of grants to their assets without replacement. Voluntary without compensation from one person to another while still alive to be owned, there is no exchange and no reason. Giving with the aim of virtue in association without expecting anything from anyone, where the surrender of ownership means that what is given is full property. So that in this study the author has set the title, namely Normative Juridical Analysis of the Decision of the Kraksaan Religious Court Number: 2308/Pdt.G/2016/Pa.Krs in Settlement of Land Grants Disputes Study Pututasa Land Lawsuit Grants Kraksaan Religious Court). From the title, it can be formulated the problem factors. How is the process of examining the cancellation of grants by the Kraksaan Religious Court and what is the legal status of the cancellation of grants by the Kraksaan Religious Court. The method used in this research is normative legal research or library research which is carried out by reviewing and reviewing library sources in the form of primary data and secondary data sources that are relevant to the discussion and help understanding. From the results of the discussion and research, it can be concluded that the plaintiff's claim is firmly rejected, because since the swah land located in Wonorejo village, Maron sub-district, Probolinggo district (the object of the dispute) belongs to the Defendant with proof of ownership being a certificate of Ownership and the authority of the Defendant, thus the lawsuit should be ruled out without needing to be considered. Keywords : Juridical Analysis, Court Decision, Grant Land Dispute